Fish waste to sustainable additives: Fish protein hydrolysates alleviate intestinal dysbiosis and muscle atrophy induced by poultry by-product meal in Lates calcarifer juvenile - Chaklader, Md Reaz; Howieson, Janet; Foysal, Md Javed; Hanif, Md Abu; Abdel-Latif, Hany M.R.; Fotedar, Ravi (Frontiers in Nutrition, 2023)
Valorising waste from the processing of fishery and aquaculture product into functional additives and subsequent use in aquafeed as supplements could be a novel approach to promoting aquaculture industry sustainability. The present study supplemented 10% of various fish protein hydrolysates (FPHs), obtained from the hydrolysis of kingfish (KH), carp (CH) and tuna (TH) waste, with 90% of poultry by-product meal (PBM) protein to spare fishmeal (FM) completely from the barramundi diet. At the end of the trial, intestinal mucosal barriers damage, quantified by villus area (VA), lamina propria area (LPA), LPA ratio, villus length (VL), villus width (VW) and neutral mucin (NM) in barramundi-fed a PBM-based diet was repaired when PBM was supplemented with various FPHs. PBM-TH diet improved these barrier functions in the intestine of fish. Similarly, FPHs supplementation suppressed PBM-induced intestinal inflammation by controlling the expression of inflammatory cytokines (TNF-α and IL-10) and mucin-relevant production gene (i-mucin C). The 16S rRNA data showed that a PBM-based diet resulted in dysbiosis of intestinal bacteria, supported by a lower abundance of microbial diversity along with a prevalence of Photobacterium. PBM-FPHs restored intestine homeostasis by enhancing microbial diversity compared to those fed a PBM diet. PBM-TH improved the diversity further by elevating the Firmicutes phylum and the Ruminococcus, Faecalibacterium, and Bacteroides genera. Muscle atrophy evaluated by fibre density, hyperplasia and hypertrophy and associated genes (IGF-1, myf5 and MyoG) occurred in barramundi fed PBM diet was repaired after supplementation of FPHs with the PBM. Similarly, creatine kinase, calcium, phosphorous and haptoglobin were impacted by PBM-based diet but restored in barramundi fed FPHs supplemented diet. Hence, using circular economy principles, functional FPHs could be recovered from the fish waste, and be applied in aquafeed formulation and could prevent PBM-induced intestinal dysbiosis and muscular atrophy.